Incorporating unstructured free play into organized sports - Barreiro, J. A.; Howard, R. (Strength and Conditioning Journal, 2017)
AB Play is an essential element of positive youth development. Youth should engage in all 3 types of play (unstructured, semistructured, and structured) to best promote physical literacy, motor skill proficiency and muscle strength, long-term athletic development, and fun. Unfortunately, however, emphasis is too often placed on structured play, such as playing on a sports team, potentially at the expense of motor skill mastery. Overuse, injury, and dropping out of sports are possible consequences of sports specialization. This article describes how play positively influences athleticism and lifetime participation in physical activity and recommends how to balance and integrate free play into sports practice